2005
DOI: 10.1089/pho.2005.23.27
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Laser Light Reduces Loading Time of Dental Implants: A Raman Spectroscopic Study

Abstract: It is concluded that LLLT does improve bone healing, and this can be safely assessed by Raman spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
178
0
10

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(207 citation statements)
references
References 22 publications
18
178
0
10
Order By: Relevance
“…The GaAlAs laser with an 830-nm wavelength was selected on the basis of successful results obtained on fibroblasts and also on osteoblasts, both in vitro and in vivo by different authors [15][16][17][33][34][35][36][37][38][39][40][41][42][43][44][45]. The infrared lasers are known to have a greater depth of tissue penetration in comparison to red or blue light [46], thus, the osteoblasts cells could better absorb the laser energy because of the low water absorption at that wavelength [33,36,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GaAlAs laser with an 830-nm wavelength was selected on the basis of successful results obtained on fibroblasts and also on osteoblasts, both in vitro and in vivo by different authors [15][16][17][33][34][35][36][37][38][39][40][41][42][43][44][45]. The infrared lasers are known to have a greater depth of tissue penetration in comparison to red or blue light [46], thus, the osteoblasts cells could better absorb the laser energy because of the low water absorption at that wavelength [33,36,45].…”
Section: Discussionmentioning
confidence: 99%
“…Little data exist concerning these effects on the osseointegration process of implants [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…These procedures would not be possible in rats or mice. 9,10,13,40 In accordance with the most recent literature, LLLT was delivered by an infrared laser [7][8][9][10][11][12][13][14][15][26][27][28]35,38 of 830 nm wavelength 7,10,[12][13][14][15] and 50 mW output power in two sites near the mandibular implant, in seven sessions 7,11,12,15 every 48 h, using three different doses. The use of a sham surgery and sham LLLT control group (C-I), as well as a baseline surgery but sham LLLT group (C-II), enabled us to isolate both the influence of baseline surgery and the systemic effects of LLLT.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated the irradiation of extraction sockets, 3 modulation of skin wound healing, [4][5][6] regeneration of nervous tissue, 5 enhancement of peri-implant tissue repair after implant placement, 2,[7][8][9][10][11][12][13][14][15][16] and modulation of postoperative pain. 2,7,[17][18][19][20][21][22][23][24] Other in vivo and in vitro studies have reported the positive effects of LLLT on the repair process in animal models and tissue cultures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation